EFEKTIFITAS TERAPI BEKAM TERHADAP PENURUNAN KADAR ASAM URAT PADA DEWASA USIA 26-45 TAHUN DI PUSKESMAS SEDAYU 1 - Rochman, Nur; Mahfud, Mahfud; Fatimah, Fatimah (Journal of Advanced Nursing and Health Sciences, 2020)
Cupping (Al-Hijamah) is a method of treatment with hemorrhage damaged, metabolism through garbage surface of the skin into the sunnah and included into Thibbun Nabawi. Now the community has often used this method as a treatment non pharmacology to cure diseases metabolic including diseases such as diseases uric acid. Research aims to understand the effectiveness of therapy cupping to a decrease in the uric acid in the adult age 26-45 years in the Clinic sedayu 1. The kind of research this is research pre his experiments with design research one group pretest-posttest without the comparison group. Population in this research is the number of patients matures by age 25-45 years out of the uric acid since December 2016 at Clinic sedayu 1. Non-random sampling technique with the methods of the total sample, the number of 30 people. Test analysis using Paired sample t-test. Results statistical tests sample paired t-tests obtained an average reduction of uric acid levels of measurement before 7,99 mg/dl and after 7,48 mg/dl cupping therapy was 0.51 mg / dl with P-value of 0.0001 (P <0.05), Then hypothesis Ha received it means there were the effectiveness of therapy cupping to a decrease in levels of uric acid before and after treatment in one observation. Cupping effective therapy to a decrease in levels of uric acid by those with that disease history now levels of uric acid (>7 mg/dl) in Clinic Sedayu 1.